Evaluation of a Wing-Type Against a Bucket-Type Fruit Fly Trap for Use in Table Grape Vineyards - Schwartz, A.; Capatos, D. (South African Journal of Enology and Viticulture, 2017)
The standard fruit fly trap (wing-type) was evaluated against a new (bucket-type) trap ou table grapes. From an initial value of 47,7%, relative effectiveness, the standard trap showed a sharp decline during the second to fourth week and reached zero within a period of eight weeks. Both the linear and quadratic terms of the regression curve of relative effectiveness against time were statistically significant. It is suggested that the standard type of trap be replaced by the new bucket-type fruit fly trap.